2017
DOI: 10.3389/fpls.2017.02014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Genetic Diversity between Chinese and American Soybean (Glycine max (L.)) Accessions Revealed by High-Density SNPs

Abstract: Soybean is one of the most important economic crops for both China and the United States (US). The exchange of germplasm between these two countries has long been active. In order to investigate genetic relationships between Chinese and US soybean germplasm, 277 Chinese soybean accessions and 300 US soybean accessions from geographically diverse regions were analyzed using 5,361 SNP markers. The genetic diversity and the polymorphism information content (PIC) of the Chinese accessions was higher than that of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 64 publications
(73 reference statements)
9
32
2
Order By: Relevance
“…These genotypes were similar in days to 50% flowering and 100 seed weight (S2). The fact that genotypes with similar flowering response were grouped together by SSR marker‐based cluster analysis gives some credence to the suggestion that the origin of genotypes is the principal factor driving differentiation in cultivated soybean (Liu et al, ; Roberts et al, ). High variation in days to flowering among the accessions studied can be exploited to develop varieties for the different agroecologies in Ghana, especially, the Guinea and Sudan savannah ecologies with monomodal rainfall pattern.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These genotypes were similar in days to 50% flowering and 100 seed weight (S2). The fact that genotypes with similar flowering response were grouped together by SSR marker‐based cluster analysis gives some credence to the suggestion that the origin of genotypes is the principal factor driving differentiation in cultivated soybean (Liu et al, ; Roberts et al, ). High variation in days to flowering among the accessions studied can be exploited to develop varieties for the different agroecologies in Ghana, especially, the Guinea and Sudan savannah ecologies with monomodal rainfall pattern.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, Zhangxiong et al, () obtained gene diversity of 0.34 despite using 5,195 SNP markers to genotype 577 accessions of soybean. Despite a large number of markers and accessions used in this study, diversity parameters reported were lower than what has been reported by most SSR marker‐based studies including the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Two iSelect Illumina Infinium BeadChip arrays are publicly available for assaying soybean SNPs: the SoySNP50K (Song et al., 2013; SoyBase, 2018) with 50,000 SNPs and the BARCSoySNP6k with SNPs selected from the SoySNP50K chip by the Soybean Genomics and Improvement Laboratory, Beltsville Agricultural Research Center, MD (Illumina, Inc., 2015; Song et al., 2014). The SoySNP50K and BARCSoySNP6k SNP sets have been used in various mapping and genetic characterization studies (Akond et al., 2013; Gibson, 2015; Huang et al., 2018; Liu et al., 2017b; Urrea, Rupe, Chen, & Rothrock, 2017). The SoySNP50K chip was also used to genotype the full 20,087 USDA soybean germplasm collection (soybean GRIN collection) (Song et al., 2015) and those SNP data were generously made available to the soybean research community (https://soybase.org/dlpages/).…”
Section: Methodsmentioning
confidence: 99%
“…However, these endemic varieties were severely destroyed in the late of the last century due to the competitive substitutes of tung oil-derived products. Wild species always have a relatively high genetic diversity, giving them more potential in genetic adaptability to a new environment [26,27], and thus they may have a high risk of invasion compared to their cultivars. For the cultivar, many genes of agronomical importance were artificially selected while a body of other genes were also lost during the process of improvement [28].…”
Section: Discussionmentioning
confidence: 99%